2016
DOI: 10.7575/aiac.alls.v.7n.3p.146
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of EFL High School Students in Using of Computer Technology in the Process of Learning: Merits and Demerits

Abstract: Recent developments in the field of computer technology have led to a renewed interest in the process of learning. In order to investigate EFL learners' perception of technology use, a mixed method design was used to explore students' attitude. Quantitative data was collected through questionnaires and qualitative data using open-ended questions.The questionnaire was distributed in two different high schools (one male and one female) in Zanjan, 2015. Participants were 340 high school students who filled in CAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Moreover, considering the level of ICT equipment both types of schools possess, which is diametrically different, public high school students are neither motivated to use ICTs in the EFL class nor ready to do so, whereas their counterparts are exactly the opposite, which is supported by Izadpanah (2016) who argues that those students who are surrounded by a technology-based learning environment tend to naturally feel more motivated and consequently, learn more easily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, considering the level of ICT equipment both types of schools possess, which is diametrically different, public high school students are neither motivated to use ICTs in the EFL class nor ready to do so, whereas their counterparts are exactly the opposite, which is supported by Izadpanah (2016) who argues that those students who are surrounded by a technology-based learning environment tend to naturally feel more motivated and consequently, learn more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Students' characteristics and perceptions Prensky (2001) defined today's students as digital natives, people who have fundamentally changed in comparison to their previous generation because they have been exposed from a very early age to different technologies in the shape of computers, videogames, or cell phones among an almost endless variety of technological advances that have helped them to effortlessly understand and interiorize the language of such technologies. This explains why Izadpanah (2016) found that students learning EFL with ICTs show a positive attitude towards the use of different technologies in the classroom and are willing and eager to keep working in such a manner.…”
Section: Teachers' Characteristics and Perceptionsmentioning
confidence: 99%
“…The important matter in using films and movies effectively depends on the teacher's ability to persuade students to receive the films` message. Some reasons for the use of films in English language teaching are (Askildson, 2005;Hoffler & Leutner, 2007;Izadpanah & Alavi, 2016;Schnotz, 2005):…”
Section: Email: Info@ijreeonlinecommentioning
confidence: 99%
“…Malaysia opened the Open University of Malaysia that caters to learners in remote regions and to those who cannot attend live lectures through m-learning (Njagi et al, 2015). Researchers from developing nations in the Middle East (Izadpanah and Alavi, 2016), Asia (Joan, 2013) and Africa (Adeyemo et al, 2013; Mtebe and Raisamo, 2014; Bachore, 2015) are calling for their respective nations to invest more into TIE. Finally, due to the effects of the coronavirus pandemic, schools globally have been relying more heavily on TIE and technology (Gyimah, 2020).…”
Section: Introductionmentioning
confidence: 99%